Disappearance of the inhibitory effect of neuropeptide Y within the dorsolateral bed nucleus of the stria terminalis in rats with chronic pain. (29th May 2020) - Hara, Ryuto; Asaoka, Yuta; Takahashi, Daiki; Nomura, Hiroshi; Amano, Taiju; Minami, Masabumi
Highlights: NPY hyperpolarized type II dlBNST neurons in sham-operated control rats. NPY depolarized type II dlBNST neurons in rats with chronic pain. This change in the NPY effect may cause abnormal activation of type II dlBNST neurons. The change may cause chronic pain-induced dysfunction of the mesolimbic reward system. Abstract: We recently showed that the mesolimbic dopaminergic system was tonically suppressed during chronic pain by enhanced corticotropin releasing factor (CRF) signaling within the dorsolateral bed nucleus of the stria terminalis (dlBNST), and that inhibition of intra-dlBNST CRF signaling restored the mesolimbic dopaminergic system function. Specifically, bilateral intra-dlBNST injections of the CRF type 1 receptor antagonist NBI27914 increased intra-nucleus accumbens dopamine release and induced reward-related behaviors in rats with chronic pain. Here, we used a conditioned place preference (CPP) test to explore whether intra-dlBNST injections of neuropeptide Y (NPY) restored the mesolimbic reward system function in chronic pain rats, because we previously showed that NPY had an effect opposite to that of CRF in dlBNST neurons. Specifically, CRF depolarized type II dlBNST neurons whereas NPY hyperpolarized them. However, unexpectedly, intra-dlBNST NPY injections had no effect on CPP test outcomes. Then, we compared the effects of NPY on the membrane potentials of type II dlBNST neurons of sham-operated control rats and those of chronic pain animals. Whole-cell patch-clamp electrophysiology revealed that NPY hyperpolarized type II dlBNST neurons in the sham-operated group. By contrast, in the chronic pain group, NPY did not hyperpolarize, but rather depolarized, type II dlBNST neurons. These results indicate that NPY no longer hyperpolarizes type II dlBNST neurons in rats with chronic pain, therefore it does not reverse the excitatory effects of CRF. This may be why intra-dlBNST injections of NPY into chronic pain rats did not exhibit a rewarding effect in the CPP test, whereas intra-dlBNST injections of NBI27914 did. This is the first study to demonstrate a chronic pain-induced neuroplastic change in NPY signaling in the dlBNST. Such a change may be involved in the dysfunction of the mesolimbic reward system under the chronic pain condition.